El Salvador : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper focuses on policies to raise growth; underpin fiscal sustainability while enhancing social safety nets; and strengthen financial sector stability, deepening, and inclusiveness. GDP growth averaged 2 percent during 2000-14, well below the Central American regional average of 4 1\2 percent. While the underlying causes of the low growth are complex, a key channel through which they are evident appears to be low investment. Given the need to increase growth, revenue-raising measures should be accompanied by cuts in distortionary taxation. Stress tests suggest that financial buffers are adequate to contain most risks. The financial deepening and advancing financial inclusion could have a meaningful impact on both growth and poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet